Thrombosis and kidney disease in cancer: comorbidities defining a very high risk patient: A position paper from the Cancer & the Kidney International Network. Issue 2 (June 2018) - Launay-Vacher, Vincent; Scotté, Florian; Riess, Hanno; Ashman, Neil; McFarlane, Philip; Ribic C, Christine Maria; Elalamy, Ismail
Cancer & the Kidney International Network was created in 2014. The aim was to improve the management of cancer patients by developing clinical and scientific knowledge on the main topic of cancer and the kidney. Therefore, the Cancer & the Kidney International Network created a special working group: the Thrombosis, Kidney Disease, and Cancer working Group. The first step of this force was to produce a position paper on this topic by investigating the association of chronic kidney disease and venous thromboembolism in cancer patients, focusing particularly on the anticoagulant management of patients presenting these three comorbidities. The use of low-molecular-weight heparins, vitamin K agonists and oral direct anticoagulants in cancer patients with chronic kidney disease was reviewed.